S100β is associated with cognitive impairment in childhood-onset systemic lupus erythematosus patients. (April 2017) - Lapa, A T; Postal, M; Sinicato, N A; Bellini, B S; Fernandes, PT; Marini, R; Appenzeller, S
Objective: To investigate serologic S100β protein levels in childhood-onset SLE patients (cSLE) and to elucidate their association with disease activity and neuropsychiatric (NP) manifestations. Methods: We included 71 cSLE patients (67 females; median age 18 years; range 9–37 and 53 (47 females; median age of 20 years; range 6–29) age and sex matched healthy controls. Neurological manifestations were analysed according to the American College of Rheumatology (ACR) criteria. Cognitive evaluation was performed in all participants using Wechsler Intelligence Scale for Children (WISC-III) and Wechsler Adult Intelligence Scale (WAIS), according to age, and validated in Portuguese. SLE patients were further assessed for clinical and laboratory SLE manifestations, disease activity (SLE Disease Activity Index (SLEDAI)), damage (Systemic Lupus International Collaborating Clinics/American College of Rheumatology Damage Index (SDI)) and current drug exposures. Sera S100β protein levels were measured by enzyme-linked immunosorbent assay using commercial kits. Results: The median S100β protein level was 116.55 pg/mL (range 1.53–468.50) in cSLE and 54.98 pg/mL (range 0.69–181.00) in healthy controls ( p < 0.001). An association was observed between S100β protein and NP manifestations ( p = 0.03). The S100β protein levels was associated with cognitive impairment in cSLE patients ( p = 0.006). Conclusions: S100β protein levels are increased in cSLE with cognitive impairment. S100β may be considered a potential biomarker that underlies central nervous system (CNS) dysfunction, especially cognitive impairment.